Pengaruh Struktur Aset, Profitabilitas, Operating Leverage Dan Likuiditas Terhadap Struktur Modal Perusahaan Consumer Goods di BEI - Dharmadi, I Komang Yusa; Dwija Putri, I Gusti Ayu Made Asri (E-Jurnal Akuntansi; Vol 24 No 3 (2018)DO - 10.24843/EJA.2018.v24.i03.p08, 2018)
Capital structure is counter balance between capital eksternal (long-range) with the self capital. The purpose of this study to determine the effect of asset structure, profitability, operating leverage and likuiditas to capital structure. The measurement this study of capital structure use the long term debt to equity ratio (LTDER). Excelsior mount the presentase LTDER indication that excelsior of debt composition compared to a equity of a company. The study focussed at consumer goods company enlisted in Effect Exchange Indonesia (BEI) Period 2010-2014. Perception amount as much 100 sampel research obtained with the method of nonprobability sampling with the technique of purposive sampling. Analysis technique used in this study is multiple linear regression analysis. The result showed that asset structure and liquidty have a positive effect to capital structure , profitability and operating leverage have a negativity effect to capital structure. Keyword: C apital structure, asset structure, profitability, operating leverage, and liquidity